Continuation rates for injectable contraception and intra-uterine device (IUD) at Banyuning Village, Buleleng District - Lina Anggaraeni Dwijayanti; Dewa Nyoman Wirawan; Anak Agung Sagung Sawitri (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: Surveys on the proportion of contraception uptake have been regularly conducted in Indonesia, including Bali Province. However, very limited studies have explored contraceptive continuation rates. This study aims to examine continuation rates for injectable contraception and IUD including its determinants. Methods: A cross-sectional survey was conducted in Buleleng District. A total of 100 reproductive age women who ever used or currently using injectable contraception or IUD were recruited to participate in the study. One village at Buleleng District was purposively selected and samples were selected from all registered reproductive age couples at the village using a systematic random sampling method. Data were collected through home interviews and were analysed using survival analysis to calculate contraceptive continuation rates. Multivariate analysis were performed using cox regression to identify factors associated to continuation rates for injectable contraception and IUD. Analysis was done using STATA SE 12.1. Results: The one year continuation rate for IUD for first child was 84.62% whereas for injectable contraception was 71.03%. When sex variable of the child was applied, the one year continuation rate for IUD for first child was higher among those who have male child (81.82%) than female child (66.67%). Similarly, the one year continuation rate for injectable contraception was higher among those who have male child (79.10%) than female child (57.58%). The one year contraceptive continuation rate is also higher for the second child than the first one (79.56 vs 71.03 for injectable and 87.88 vs 84.62 for IUD). The multivariate analysis showed that perceived quality of family planning services was associated to contraceptive continuation rates (AHR=2.54; 95%CI: 1.22-5.29). Conclusions: The continuation rate for IUD was higher than injectable contraception. Higher contraceptive continuation rate was found among those who have male children. The contraceptive continuation rate was associated with perceived quality of family planning services. Interventions to improve the quality of family planning services are warranted.